Five new species of Hypseloecus Reuter (Hemiptera: Miridae) on hemiparasitic Santalales from India - Yeshwanth, H. M. (Zootaxa, 2014)
Five new species of Hypseloecus viz., Hypseloecus acutus sp. nov., Hypseloecus articulatus sp. nov., Hypseloecus belli sp. nov., Hypseloecus orientale sp. nov. and Hypseloecus spinosus sp. nov. are described from India. The genus is recorded for the first time from India collected on hemiparasitic plants of the genera Dendrophthoe and Viscum (Santalales). A key to identification of the five species has been provided with descriptions of the male genital structures, digital microscopic images and also photographic images of live individuals.